PENGARUH KUALITAS SDM, KOMITMEN ORGANISASI, PEMANFAATAN TEKNOLOGI INFORMASI PADA EFEKTIVITAS PENERAPAN SAP BERBASIS AKRUAL - Arta, Kadek Agus Yogi; Yadnyana, I Ketut (Buletin Studi Ekonomi; VOL.24.NO.1.FEBRUARI 2019DO - 10.24843/BSE.2019.v24.i01.p09, 2019)
Abstract: Effect of Quality of Human Resources, Organizational Commitment, Use of Information Technology on the Effectiveness of Accrual-Based SAP Implementation. Based on knowing the influence of the quality of human resources, organizational commitment, and the application of information technology on the effectiveness of applying accrual-based government accounting standards to SKPD Karangasem Regency. As many as 134 civil servants in the financial section are the population as well as samples from this study because the sampling technique used is saturated samples. multiple linear regression is the analysis techniques that used in this study,and the results show that the quality of HR, organizational commitment and the application of information technology have a positive influence on the effectiveness of accrual-based SAP implementation in the SKPD of Karangasem Regency.